EFFECT OF MUSIC THERAPY TO DECREASE THE ELDERLY IN INSOMNIA UPT ELDERLY SOCIAL SERVICES DISTRICT PASURUAN BABAT LAMONGAN - Pratiwi, Diana; Kurniawan, Vendi Eko; Hariyono, Rudi (LPPM STIKes Bahrul Ulum Jombang, 2016)
Javanese music as therapy to reduce insomnia , because Javanese music is a music that contains elements of culture with the strains of soft then the elderly will feel calm and comforlable when listening so relaxed . Because music therapy is one of the efforts to improve the quality of the physical , mental, social, and economic. The research objective was to determine the effect of music therapy Java to decrease insomnia m elderly UPT PLSU. This research uses experimental desampra-, with a model approach to pre-post test within a group (one-group pre-post test design). With a population of 20 people. The samples were elderly living in UPT. PSLU of 20 people with a total sampling technique method. Questionnaire data collection use Biological Psychiatry Study Group Jakarta - Insomnia Rating Scale (KSPBJ-IRS) .Before do music therapy Java there were 9 (45%) with moderate insomnia, after doing music therapy Java there were 8 (40%) with mild insomnia. Statistical analysis using the Wilcoxon Signed Rank Test with SPSS-WS 16 0 is rejected then the result 1s the value of Z = -4123 p = 0.000 so that H1 is accepted. This shows that there is a Java Music Therapy Effect in UPT of Elderly Social Services Sub Pasuruan m Babat Lamongan. It is expected from these results that insorr,nia can be solved with be given Javanese music therapy in elderly UPT PLSU of Pasuruan Babat Lamongan Keywords : Java Music Therapy, Insomnia In Elderly